H2O2 oxidative activity: modulatory effect of hydroxytyrosol - Incani, A.; Deiana, M.; Atzeri, et al., A. (Progress in Nutrition, 2013)
Hydroxytyrosol (HT) is the major o-diphenol present in extra-virgin olive oil, either in free or esterified form, once absorbed, is present in high amount in the kidney, where it may exert a proctetive action. In this study we monitored the ability of HT to protect renal cells (LLC-PK1) against oxidative damage induced by H2O2. The peroxidation of lipid represents a primary consequences of cellular oxidative stress, leading to biophysical changes that disrupt membrane and organelle function; moreover oxidative stress is a process that may stimulate cellular signalling pathways, usually associated with the promotion of cellular death. HT exerted a significant antioxidant action, inhibiting the production of fatty acids hydroperoxides and 7-ketocholesterol induced by H2O2 treatment and thus preserving the membrane lipids. It has been shown that oxidative stress in LLC-PK1 cells is related also to the changes in the phosphorylation state of pro-death signalling pathways ERK1/2 and the pro-survival signalling Akt/PKB. Pretreatment with HT is able to modulate H2O2-induced changes in the phosphorylation state of ERK1/2 and Akt/PKB. We suggest that one potential protective mechanism of olive oil polyphenols in kidney cells may be attributed to interactions with intracellular signalling pathways activated in response to oxidative stress. Azione ossidante del H2O2: effetto modulatorio dell’idrossitirosolo L’idrossitirosolo (HT) è uno dei maggiori fenoli semplici presenti nell’olio extravergine d’oliva, presente in forma libera o coniugata; assunto con la dieta l’HT viene assorbito concentrandosi preferenzialmente a livello renale dove potrebbe esercitare un’azione protettiva. Lo scopo di questo lavoro è stato quello di valutare l’attività protettiva dell’HT contro il danno ossidativo indotto dal H2O2 in colture di cellule renali (LLCPK1). La perossidazione lipidica rappresenta la conseguenza primaria dello stress ossidativo, ma lo stress ossidativo può agire anche indirettamente su vari pathways intracellulari e andare quindi ad interferire con i meccanismi di sopravvivenza o apoptosi. Il pretrattamento delle cellule LLC-PK1 con HT ha mostrato la capacità di prevenire la perossidazione lipidica indotta dal H2O2, inibendo in maniera significativa la formazione di prodotti di ossidazione. È stato dimostrato che lo stress ossidativo è correlato con l’attivazione di ERK e della proteina chinasi B/Akt (Akt/PKB), la cui modulazione regola la sopravvivenza o l’apoptosi della cellula. L’HT sembra inibire il cambiamento di fosforilazione indotto dal H2O2, delle proteine considerate. I dati ottenuti confermano che l’HT nelle cellule renali, è in grado di esercitare un’azione protettiva, agendo sia da scavenger ma anche attraverso un meccanismo più complesso, che comporta l’interazione con i pathways intracellulari modulati dallo stress ossidativo.